Culture as Administrative Infrastructure: Crisis Governance and Community Recovery After the Maui Wildfires - Lauren Azevedo; Ratna B. Dougherty; Kaila Witkowski; Christa L. Remington (The American Review of Public Administration, 2026)
Despite growing attention to culture in public administration responses to crisis events, culture is often treated as background context rather than as part of the administrative infrastructure through which governance occurs. This article extends the theory of administrative capacity by arguing that culture can function as administrative infrastructure in post-disaster public management. Using qualitative interviews with community members, grassroots organizers, and nonprofit leaders in Maui, as well as public forum data collected within 12 months of the 2023 Maui wildfires, we examine how culture shaped legitimacy, coordination, authority, and recovery capacity in the aftermath of disaster. Findings show that culturally grounded relationships to land, water, community, and history shaped how residents interpreted formal recovery efforts, mobilized outside government systems, asserted authority over rebuilding, and defined what recovery should mean. We develop a culture as administrative infrastructure framework that shows how culturally grounded forms of authority, resistance, and place-based knowledge reveal the limits of culturally neutral administrative systems. The article contributes to public administration theory by showing that administrative capacity is not only built through agencies, resources, procedures, and networks, but also through culturally embedded systems of legitimacy, knowledge, authority, and collective care.